2020
DOI: 10.1088/1361-6579/abc4c6
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of the two-point discrimination test on the sole of the foot in people with multiple sclerosis

Abstract: Background: Two-point discrimination (TPD) is an assessment of tactile acuity. People with multiple sclerosis (MS) can have reduced foot sole tactile acuity, which has been linked to impaired balance. Objective: To quantify the test–retest reliability of TPD on the sole of the foot in people with MS. Approach: 41 participants (32 females), with mean (SD) age of 60 (9) years, and Expanded Disability Status Scale of <7.5, had their TPD measured at the head of the first metatarsal and the heel on two occasions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…To help health care professionals select the optimal tests of sensibility, there have been ongoing discussions on the psychometric properties of sensibility tests, such as reliability and validity, in a variety of injuries and other neurologic conditions. 19 , 20 , 21 , 22 However, in the context of upper limb PNI, there still exist uncertainties in choosing the optimal sensibility tests. For example, Jerosch-Herold 4 identified that 2-PD has limited validity and responsiveness yet remains widely used in the PNI setting.…”
mentioning
confidence: 99%
“…To help health care professionals select the optimal tests of sensibility, there have been ongoing discussions on the psychometric properties of sensibility tests, such as reliability and validity, in a variety of injuries and other neurologic conditions. 19 , 20 , 21 , 22 However, in the context of upper limb PNI, there still exist uncertainties in choosing the optimal sensibility tests. For example, Jerosch-Herold 4 identified that 2-PD has limited validity and responsiveness yet remains widely used in the PNI setting.…”
mentioning
confidence: 99%